Assessment of genetic diversity based on quality and morphological characters in spring wheat (Triticum aestivum L em Thell) - Eyebernova, Shemshat; Sharma, Ram Kumar; Singh, Anju M; Ahlawat, Arvind K; Kala, Y K (Journal of Cereal Research, 2018)
In the present study, 64 genotypes differentiate into nine multi genotypic clusters based on quality and morphological characters. Identification of promising and genetically diverse genotypes for different traits which can be used in hybridization programme for getting a wide spectrum of variability and transgressive segregants for quality and other traits. Clustering pattern revealed that genetic diversity was not related either with geographical diversity or pedigree of the genotypes. DOI:10.25174/2249-4065/2018/78823